Teen and Social Violence in Cinema: Construction of Teen Identity in Film Dilan 1990 - Euis Komalawati (Ikatan Sarjana Komunikasi Indonesia, 2020)
Dilan 1990 is a teenage film with the highest number of viewers in 2018, which reached 6,315,664.Â The success ofÂ Dilan 1990 is inseparableÂ from the culture industry's strength, which can mobilize public interest through reliable publication and marketing. The success of the film Dilan carrying the characters of Dilan and Milea as teen idols raises concerns about the identity of adolescents who are laden with violent symbols. This is because the content and theme of the story in the 1990s were constructed with Dilan's character, who liked to fight. For this reason, this study aims to analyze the construction of adolescent identity and social violence in the 1990 Dilan film. This research method uses a qualitative approach with an interpretative paradigm. Data Analysis Method uses narrative analysis of film subtitles with the Vladimir Propp analysis model. The unit of analysis in this study is the film Dilan 1990 (2018). Data collection techniques are conducted with text analysis, literature study, observation, and documents. This study concludes that social violence among adolescents is constructed in the cinema through adolescents' identity, both verbal violence and physical violence in the school environment and outside of school. Young men carry out social violence to young women who describe gender inequality, which refers to social violence due to cultural factors.